The Effect of Date Palm (Phoenix Dactylifera) Juice to Prevent Stunting - Dewi Nurviana Suharto; Nirva Rantesigi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: One of the problems due to lack of chronic nutrient intake in toddlers is stunting. Stunting can be prevented by fulfilling nutritional intake with nutrient-rich foods such as date juice, because date juice is a good source of carbohydrates, amino acids, minerals, and dietary fiber to meet the body's nutritional needs, especially in toddlers. This study aims to determine the effect of date juice on the prevention of stunting in children under five. Methods: The research design used was quasi-experimental with a two group Pretest-Posttest control group design. A total of 78 children under five who were measured for length and weight consisted of 34 people in the intervention group by giving date juice and 34 people in the control group without giving date juice. Result: The study was conducted for 3 months. After the intervention, the average body length and body weight in the intervention group increased to 12.91 for body length and 87.67 for body weight. While body length and body weight in the control group did not experience significant changes. The results of the paired t test showed a significant p-value of (<0.05) while in the control group the p value was> 0.05, meaning that there was no change in body length and body weight in the control group. Conclusion: This study shows that date juice has an effect in preventing stunting. Based on the results of this study, nurses need to maximize stunting prevention education by meeting nutritional needs by consuming nutrient-rich foods such as date juice.